A Qualitative Error Analysis and Its Pedagogical Implications - Rosalia Arofatul Ihsani; Yunus Sulistyono (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: The ability to write in accordance with Indonesian language rules is an important indicator of students' academic literacy competence in the global era. However, many students still make linguistic errors in writing expository texts. This study aims to (1) describe the writing patterns of expository texts produced by tenth-grade students of SMK Negeri 1 Karanganyar and (2) identify the types of language errors that frequently occur in their writing.Methodology: This research employed a qualitative descriptive approach. The data sources consisted of thirty expository texts written by students from two vocational programs, namely Accounting and Office Affairs. Data were collected through documentation and interview techniques, and analyzed using Miles and Huberman's interactive model, which includes data reduction, data display, and conclusion drawing.Results: The findings reveal four categories of language errors: spelling, morphology, syntax, and semantics. The most dominant errors occurred in spelling and morphology, particularly in capitalization, prepositional usage, and non-standard word formation. The contributing factors include informal writing habits developed through social media, regional language interference, and low awareness of the General Guidelines for Indonesian Spelling (PUEBI).Applications/Originality/Value: This study provides significant pedagogical implications for Indonesian language learning, particularly in implementing error-based learning strategies that encourage reflection and systematic correction of students' linguistic errors. The originality of this study lies in its focus on vocational high school contexts, providing insights into how language awareness can be enhanced to improve writing accuracy among vocational students.